Choosing wisely for thyroid conditions: Recommendations of the thyroid department of the Brazilian society of endocrinology and metabolism - Dora, Jose Miguel; Biscolla, Rosa Paula Mello; Caldas, Gustavo; Cerutti, Janete; Graf, Hans; Hoff, Ana O.; Mazeto, Glaucia M. F. S. [UNESP]; Magalhães, Patrícia Kunzle Ribeiro; Mesa Junior, Cleo Otaviano; Scheffel, Rafael Selbach; Dos Santos Teixeira, Patricia De Fatima; Vaisman, Fernanda; et al. (Archives of Endocrinology and Metabolism, 2021)
Objective: Choosing Wisely (CW) is an initiative that aims to advance the dialogue between physicians and patients about low-value health interventions. Given that thyroid conditions are frequent in clinical practice, we aimed to develop an evidence-based list of thyroid CW recommendations. Materials and methods: The Thyroid Department of the Brazilian Society of Endocrinology and Metabolism (SBEM) named a Task Force to conduct the initiative. The Task Force work was based on an electronic Delphi approach. The 10 recommendations that received the highest scores by the Task Force were submitted for voting by all SBEM associates. The 5 recommendations that received the highest scores by SBEM associates are presented herein. Results: The Task Force was composed of 14 thyroidologists from 10 tertiary-care, teaching-based Brazilian institutions. The brainstorming/ideation phase resulted in 69 recommendations. After the removal of duplicates and recommendations that did not adhere to the initiative’s scope, 35 remained. Then the Task Force voted to attribute a grade (0 [lowest agreement] to 10 [highest agreement]) for each recommendation. The 10 recommendations that received the highest scores by the Task Force were submitted to all SBEM associates. A total of 683 associates voted electronically, attributing a grade (0 to 10) for each recommendation. The 5 recommendations that received the highest scores by the SBEM associates compose our final list. Conclusion: A set of recommendations to avoid unnecessary medical tests, treatments, or procedures for thyroid conditions are offered with a transparent methodology. This initiative aims to foster productive interactions between physicians and patients, stimulating shared decision-making.
Keywords: Choosing Wisely; Endocrinology; Overuse; Thyroid